Chen Wen‐chen's academic contributions. Issue 6 (28th November 2021) - Chao, Anne
Abstract : Probability models for Zipf's law; asymptotic theories in urn models; optimal stopping‐time theories in urn models; and inter‐disciplinary collaboration.